Narrow-spectrum resource-utilizing bacteria drive the stability of synthetic communities through enhancing metabolic interactions - Wang, Wei; Xia, Yanwei; Zhang, Panpan; Zhu, Mengqing; Huang, Shiyi; Sun, Xinli; Xu, Zhihui; Zhang, Nan; Xun, Weibing; Shen, Qirong; Miao, Youzhi; Zhang, Ruifu (Nature communications, 2025)
The importance of synthetic microbial communities in agriculture is increasingly recognized, yet methods for constructing targeted communities using existing microbial resources remain limited. Here, six plant-beneficial bacterial strains with distinct functions and rhizosphere resource utilization profiles are selected to construct stable, multifunctional communities for plant growth promotion. Metabolic modeling reveals that narrower resource utilization correlates with increased metabolic interaction potential and reduced metabolic resource overlap, contributing to greater community stability. Integrated analyses further consistently confirm the central roles of narrow-spectrum resource-utilizing strains, Cellulosimicrobium cellulans E and Pseudomonas stutzeri G, which form metabolic interaction networks via secretion of asparagine, vitamin B12, isoleucine, and their precursors or derivatives. Two synthetic communities, SynCom4 and SynCom5, have high stability in the tomato rhizosphere and increase plant dry weight by over 80%. Our study elucidates the relationship between resource utilization width and community stability, providing a rational strategy for designing stable, multifunctional microbial communities for specific habitats. Methods for constructing targeted synthetic communities using existing microbial resources remain limited. Here, the authors report a genome-scale metabolic model-integrated strategy for bottom-up construction of synthetic microbial communities in the plant rhizosphere.